DEVELOPMENT OF POP-UP BOOK MEDIA TO IMPROVE THEMATIC LEARNING OUTCOMES IN GRADE III SD - Danindra Anindita; Naniek Sulistya Wardani (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2025)
This study aims to determine whether pop-up book media is feasible to use in problem-based learning; whether pop-up book media can be trusted for problem-based learning and whether pop-up book media in problem-based learning can improve learning outcomes of grade III elementary school students. The research was conducted at SD Negeri Salatiga with research subjects of grade III students totaling 90 students with details of 20 students in individual trials, 30 students in limited trials and 40 students in broad implementation tests. The type of research is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, implementation, Evaluating. Validation by expert lecturers and implementation test to students. Data collection techniques with tests and questionnaires, with instruments in the form of items and questionnaire sheets. This research resulted in: 1) pop-up book media that is feasible to use in problem-based learning as indicated by validation of 0.4438; 0.361; and 0.321; 2) pop-up book media can be trusted for problem-based learning as indicated by alpha = 0, 848 ˃ 0.600 which means very reliable and pop-up book media in problem-based learning can improve the learning outcomes of grade III elementary school students as indicated by the completeness of learning from pre-cycle of 30%, cycle 1 67% and cycle II 87%.